Child health promotion from the perspective of family health strategy nurses - Aline Biondo Alcantara; Lilian de Lima; Marli Teresinha Cassamassimo Duarte; Cristina Maria Garcia de Lima Parada; Vera Lúcia Pamplona Tonete (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To apprehend nurses' conceptions and experiences about actions of child health promotion in family health units. Methods Exploratory study, with thematic content analysis of statements, obtained through semi-structured interviews with 11 nurses from a municipality in São Paulo. Results Three thematic categories emerged on child health promotion actions: they must be contextualized, provide for comprehensive care, and aim at self-care; they are carried out through health guidelines shared by professionals with children and their families, inside and outside the health units; present challenges to be overcome by health services, such as lack of involvement and appreciation of the family regarding child follow-up. Conclusions The concepts apprehended approached the premises of official documents on health promotion; however, practical experiences included difficulties related to the life contexts of children, their families and health services, compromising the achievement of comprehensive care.